The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/ijerph19084677
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Morbidities, Depression, Anxiety, and Stress on Oral Health-Related Quality of Life among Migrant Elderly Following Children in Weifang, China

Abstract: This study explored the relationship between depression, anxiety, stress, morbidity, and oral health-related quality of life (OHRQoL) in the migrant elderly following children (MEFC) in Weifang, China. A total of 613 MEFC were selected using multistage cluster random sampling. The GOHAI scale was used to evaluate oral health-related quality of life. The DASS-21 scale was used to assess levels of depression, anxiety, and stress. Univariate analysis and binary logistic regression were used to analyze the correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
0
1
0
1
Order By: Relevance
“…Установлено, что пациенты с депрессией реже посещали стоматолога, чем пациенты без депрессии (р < 0,001), взрослым с депрессией и тревогой чаще удаляли зубы, по крайней мере один зуб (р < 0,001). В статье [25], посвященной изучению здоровья полости рта пожилых китайских мигрантов, показано, что существовала ассоциация с плохим состоянием полости рта у пациентов с депрессией (p = 0,012), тревогой (p = 0,026), артериальной гипертензией (p = 0,004), заболеваниями желудочно-кишечного тракта (p = 0,007) и недостаточным (начальным) уровнем образования. В другом исследовании с 500 участников старше 65 лет [26] продемонстрировано, что тяжесть депрессии ассоциирована с увеличением количества отсутствующих зубов, количеством зубов, пораженных кариесом и сухостью во рту.…”
Section: эмоциональный статус и здоровье полости ртаunclassified
“…Установлено, что пациенты с депрессией реже посещали стоматолога, чем пациенты без депрессии (р < 0,001), взрослым с депрессией и тревогой чаще удаляли зубы, по крайней мере один зуб (р < 0,001). В статье [25], посвященной изучению здоровья полости рта пожилых китайских мигрантов, показано, что существовала ассоциация с плохим состоянием полости рта у пациентов с депрессией (p = 0,012), тревогой (p = 0,026), артериальной гипертензией (p = 0,004), заболеваниями желудочно-кишечного тракта (p = 0,007) и недостаточным (начальным) уровнем образования. В другом исследовании с 500 участников старше 65 лет [26] продемонстрировано, что тяжесть депрессии ассоциирована с увеличением количества отсутствующих зубов, количеством зубов, пораженных кариесом и сухостью во рту.…”
Section: эмоциональный статус и здоровье полости ртаunclassified
“…The sum scores of 0-9 for depression, 0-7 for anxiety, and 0-14 for stress were considered normal, while the sum score of 10-42 for depression, 8-42 for anxiety, and 15-42 for stress were considered as depressed, anxious, and stressed [40]. DASS-21 has been proven to be a reliable and effective measure for assessing the mental health of the Chinese population [41,42].…”
Section: Mental Healthmentioning
confidence: 99%
“…Migration is an extremely stressful phenomenon that produces significant levels of anxiety and depressive symptoms ( Bhugra, 2004 ; Levecque et al, 2007 ; Familiar et al, 2011 ). Previous studies in China have identified a significant increase in the prevalence of anxiety and depression among elderly migrants, which has become an important issue affecting their quality of life ( Yu and Liu, 2018 ; Li and Kong, 2022 ). Compared with the local elderly, elderly migrants face low levels of social interaction ( Lin et al, 2020 ), and lack of contact with friends.…”
Section: Introductionmentioning
confidence: 99%